City CarShare: Assessment of Short-Term Travel-Behavior Impacts - Nina Creedman; Robert Cervero; Muhammad Pohan; Madhav Pai (University of California, Institute of Urban and Regional Development (IURD), 2002)
In this report, the short-term travel-behavior impacts of car-sharing in the city of San Francisco are evaluated. San Francisco's program, City CarShare, was launched in early- March 2001 and has steadily gained popularity as more and more residents as well as non-residents have voluntarily joined the program. For purposes of studying "before-and- after" changes in travel demand, data were compiled both prior to program implementation and three to four months into the program. To remove the influences of other factors that could explain changes in travel demand besides car-sharing itself, a controlled experimental framework was adopted. This involved comparing changes in travel demand between City CarShare participants and an otherwise comparable group of non-participants over time. Besides evaluating impacts, car-sharing is profiled in terms of trip purposes, travel durations, spatial patterns of trip-making, and other attributes.
Keywords: 330